Culture’s life: The responsible care for life and its existential conditions - Güitrón Torres, Rafael (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Human life is culture that is forged in the exchange that takes place between cultural subjects rooted in a natural environment. For this reason, life is the source that enables the potentialities of culture, based on its own conditions. Indeed, in the face of today’s ecological problem, human beings are called to seek solutions from the care of life and respect for the entropic limits of the biosphere. Likewise, culture for life is an inescapable task for man, from the historical-biographical, ontic-epistemic and environmental presuppositions, under penalty of endangering his own existence and that of other species that coexist with us in the planet Earth.